Limiting sender's information in Bayesian persuasion - Shota Ichihashi (Bank of Canada, 2019)
This paper studies how the outcome of Bayesian persuasion depends on a sender's information. I study a game in which, prior to the sender's information disclosure, the designer can restrict the most informative signal that the sender can generate. In the binary action case, I consider arbitrary preferences of the designer and characterize all equilibrium outcomes. As a corollary, I solve a problem of how to maximize a receiver's payoffs by restricting the sender's information: Whenever the designer can increase the receiver's payoffs by restricting the sender's information, the receiver-optimal way coincides with an equilibrium of the game in which the receiver persuades the sender.
Keywords: D82; D83; 330; Economic models